2003
DOI: 10.1074/jbc.m303170200
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation Disrupts Elongin Interaction and Accelerates SOCS3 Degradation

Abstract: The suppressors of cytokine signaling (SOCS) are negative feedback inhibitors of cytokine and growth factorinduced signal transduction. The C-terminal SOCS box region is thought to regulate SOCS protein stability most likely via an elongin C interaction. In the present study, we have found that phosphorylation of SOCS3 at two tyrosine residues in the conserved SOCS box, Tyr 204 and Tyr 221 , can inhibit the SOCS3-elongin C interaction and activate proteasome-mediated SOCS3 degradation. Jak-mediated phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 49 publications
10
109
0
Order By: Relevance
“…Tyrosine phosphorylation of SOCS3 on Y204 and Y221 residues blocks interaction with Elongin C and directs SOCS3 to degradation. Thus, this suggests a mechanism whereby tyrosine kinases can escape negative feedback control from SOCS3 by phosphorylation on specific tyrosine residues [96].…”
Section: Socs Proteins In Rtk Regulated Diseasesmentioning
confidence: 95%
See 1 more Smart Citation
“…Tyrosine phosphorylation of SOCS3 on Y204 and Y221 residues blocks interaction with Elongin C and directs SOCS3 to degradation. Thus, this suggests a mechanism whereby tyrosine kinases can escape negative feedback control from SOCS3 by phosphorylation on specific tyrosine residues [96].…”
Section: Socs Proteins In Rtk Regulated Diseasesmentioning
confidence: 95%
“…While these proteins generally controls receptor signaling by destabilizing receptor or its substrate proteins, they can also cooperate with receptors in mediating mitogenic signaling. In some cases receptors can escape negative regulation by phosphorylation on specific tyrosine residues as demonstrated in the case of SOCS3 [96].…”
Section: Socs Proteins In Rtk Regulated Diseasesmentioning
confidence: 99%
“…Previous reports have shown that SOCS-3 is phosphorylated on tyrosine residues in response to cytokines and growth factors. 27,28 Phosphorylation influences SOCS-3's ability to interact with the RasGAP and Elongin B/C proteins 28,29 and is thus potentially important for proper function of SOCS-3. In our control experiment, treatment of COS-1 cells transiently transfected with wt SOCS-3 with the protein-tyrosine phosphatase inhibitor sodium pervanadate indeed resulted in detection of high levels of tyrosine phosphorylated SOCS-3 ( Figure 3a).…”
Section: Socs-3 In Ctclmentioning
confidence: 99%
“…The SOCS box has been demonstrated to regulate the stability of SOCS proteins as well as SOCS-interacting molecules (4,14,15,37). SOCS1 accelerates the degradation of Jak1, Jak2, a TEL-Jak2 oncogenic fusion protein, the GEF Vav, and IRS-1 and IRS-2 (16 -20).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids, Antibodies, and Fusion Proteins-C-terminally FLAGtagged or HA-tagged wild-type and mutant SOCS3 cDNAs cloned into the mammalian expression vector pME18S and the retroviral expression vector pMX-IRES-GFP have been described previously (36,37). SOCS3 pY 204 /pY 221 peptide spanning amino acids 200 -225 (DSpYEKVTQLPGPIREFLDQpYDAPL) as well as pY 204 and pY 221 singly phosphorylated peptides and unphosphorylated controls were supplied by Research Genetics.…”
Section: Methodsmentioning
confidence: 99%